MODERN ASPECTS OF VACCINES TRANSPORTATION IN THE COLD CHAIN SYSTEM - Klymenko, V.V.; Yeroshenko , O.R.; Lozova , G.M.; Klymenko, I.V. (The actual problems of regional economy development, 2025)
The article is devoted to the analysis of the features of vaccine transportation in the cold chain system. The purpose of the article is to analyze the regulatory requirements and best practices for organizing vaccine transportation to preserve their quality and ensure efficiency on the way from the manufacturing enterprise to the end consumer. The authors paid significant attention to the issue of regulating and standardizing the conditions and requirements for storage and transportation of vaccines. For this purpose, international and state regulatory bodies of Ukraine (both in the field of medicine and in the field of transport) were systematized. They develop rules and standards for organizing vaccine transportation and provide comprehensive control over their quality, as well as guarantee that, if the requirements are properly met, the vaccines will not lose their effectiveness. Thanks to the analysis of the transport characteristics of vaccines, external factors affecting their quality were identified. Vaccine transportation requires strict compliance with the requirements of the cold chain using specialized refrigeration equipment and equipment for constant temperature monitoring. The quality of vaccines is also significantly affected by operations to prepare them for transportation, in particular, packaging and labeling. Transport packaging should provide proper protection of the cargo from external factors and safety during delivery. Authors` scheme of the cold chain for the supply of vaccines to Ukraine in wartime, which is based on the principles of safety and efficiency, represents scientific interest. The authors represented in practice the proposals for the organization of the activities of transport and logistics companies for the transportation of vaccines, which include regarding the requirements for the use of refrigerated rolling stock, special refrigeration and metrological equipment, the involvement of specially trained personnel, proper transport packaging and labeling, optimization of routes to comply with the estimated delivery time, and constant temperature monitoring.